Immunoreactive Proteins of Bifidobacterium longum ssp. longum CCM 7952 and Bifidobacterium longum ssp. longum CCDM 372 Identified by Gnotobiotic Mono-Colonized Mice Sera, Immune Rabbit Sera and Non-immune Human Sera - Górska, Sabina; Dylus, Ewa; Rudawska, Angelika; Brzozowska, Ewa; Srutkova, Dagmar; Schwarzer, Martin; Razim, Agnieszka; Kozakova, Hana; Gamian, Andrzej (Frontiers in Microbiology, 2016)
The Bifidobacteria show great diversity in the cell surface architecture which may influence the physicochemical properties of the bacterial cell and strain specific properties. The immunomodulatory role of bifidobacteria has been extensively studied, however studies on the immunoreactivity of their protein molecules are very limited. Here, we compared six different methods of protein isolation and purification and we report identification of immunogenic and immunoreactive protein of two human Bifidobacterium longum ssp. longum strains. We evaluated potential immunoreactive properties of proteins employing polyclonal sera obtained from germ free mouse, rabbit and human. The protein yield was isolation method-dependent and the reactivity of proteins detected by SDS-PAGE and Western blotting was heterogeneous and varied between different serum samples. The proteins with the highest immunoreactivity were isolated, purified and have them sequenced. Among the immunoreactive proteins we identified enolase, aspartokinase, pyruvate kinase, DnaK (B. longum ssp. longum CCM 7952) and sugar ABC transporter ATP-binding protein, phosphoglycerate kinase, peptidoglycan synthethase penicillin-binding protein 3, transaldolase, ribosomal proteins and glyceraldehyde 3-phosphate dehydrogenase (B. longum ssp. longum CCDM 372).